Soil macrofauna as a soil quality indicator in native and replanted Araucaria angustifolia forests - Pereira J.M. (2017)
© 2017, Revista Brasileira de Ciencia do Solo. All rights reserved.Studies on soil quality in Araucaria forests contribute to understanding changes in this ecosystem and serve as a tool in conserving its biodiversity. The aim of this study was to evaluate the potential of soil macrofauna in discriminating native and replanted Araucaria forests for selection of soil quality indicators. Native (NF) and replanted (RF) Araucaria angustifolia forests were evaluated in three regions of the state of São Paulo, representing three true replications. Fifteen soil samples were collected in each area for evaluation of the physical, chemical, and microbiological properties and the macrofauna through use of monolith excavation and the manual screening method [Tropical Soil Biology and Fertility (TSBF) method]. In addition, we evaluated the weight of the surface litter dry matter and the C, N, and S contents. The abundance of macrofauna was subjected to Principal Components Analysis (PCA) and the physical, chemical, and microbiological properties were used as explanatory environmental variables for changes in the soil community. These variables and the macrofaunal properties were applied in analyses of variance and in canonical discriminant analysis (CDA) to indicate the best properties for discrimination of the forests studied. The abundance of macrofaunal groups was influenced by the state of conservation of the forest and by the sampling period; the native forest and the summer season provided greater diversity of taxonomic groups. The richness of taxonomic groups was the property that most contributes to discriminating reforested areas from native forests. The Oligochaeta group was a prominent indicator of soil quality and/or environmental disruption in Araucaria forests. Soil moisture, total porosity, and S content in the surface litter were likewise variables that contributed to distinguishing the areas. The ecological indexes (diversity, dominance, and equitability) were not sensitive to the changes in macrofaunal properties in the forests studied.